2014
DOI: 10.3386/w20402
|View full text |Cite
|
Sign up to set email alerts
|

From Assortative to Ashortative Coupling: Men's Height, Height Heterogamy, and Relationship Dynamics in the United States

Abstract: Studies of online dating suggest that physical attraction is a key factor in early relationship formation, but say little about the role of attractiveness in longer-term relationships. Meanwhile, assortative coupling and exchange models widely employed in demographic research overlook the powerful sorting function of initial and sustained physical attraction. This article observes the effects of one physical characteristic of men-height-on various relationship outcomes in longer-term relationships, including s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Thereby, shorter men may have fewer children than men who are taller. A recent study by Weitzman and Conley () using data from 4,500 families between 1968 and 2011 (the Panel Study of Income Dynamics) showed that short men were more likely to enter relationships in which they were the same height or shorter than their spouses. In addition, it appeared that taller men tended to couple with older women, while shorter men coupled with younger women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thereby, shorter men may have fewer children than men who are taller. A recent study by Weitzman and Conley () using data from 4,500 families between 1968 and 2011 (the Panel Study of Income Dynamics) showed that short men were more likely to enter relationships in which they were the same height or shorter than their spouses. In addition, it appeared that taller men tended to couple with older women, while shorter men coupled with younger women.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it appeared that taller men tended to couple with older women, while shorter men coupled with younger women. Furthermore, Weitzman and Conley () noticed that short men tended to be in more stable marriages than average and tall men, and the incidence of divorce was found to be 32% lower among short than among average men. In this context, our findings of higher fertility among shorter husbands and taller wives couples are not surprising.…”
Section: Discussionmentioning
confidence: 99%
“…Taller men are less likely to stay lonely, and loneliness is associated with increased mortality rates in men but not in women (Kandler et al 2007), as they marry more frequently and earlier in life compared with shorter men (Weitzman and Conley 2014). Taller men have also greater reproductive success mainly because women find them more attractive.…”
Section: The Role Of Biosocial Factors In Human Longevitymentioning
confidence: 99%
“…On the other hand, shorter men tend to be in more stable marriages. In general, taller men are at higher risk of unstable marriage and divorce (Weitzman and Conley 2014). In general, taller men are healthier than shorter ones, and married men are generally healthier than single men, not only because of the "protective role of marriage", but also as a result of selection to marriage, in which women prefer men with better health, higher socioeconomic status, and lower testosterone level (Trivers 1985;Umberson 1992;Bereczkei et al 1997).…”
Section: The Role Of Biosocial Factors In Human Longevitymentioning
confidence: 99%
“…A growing literature documents the importance of physical attractiveness in romantic, marital, and sexual relationships. Several recent studies have examined the implications of measures of attractiveness for intimate relationships (e.g., McClintock, 2014;Weitzman & Conley, 2014) and document a "love premium" for beauty in which physically attractive people (as measured by height, weight, or facial beauty) are more likely to be in marital, dating, and sexual heterosexual relationships. While intriguing, these studies tend to focus on adolescence through middle age, and thus generate additional questions, particularly regarding how sustained the advantages of early life attractiveness are across the life course.…”
mentioning
confidence: 99%